Highly conductive proton-conducting electrolyte with a low sintering temperature for electrochemical ammonia synthesis. (18th March 2020) - Lei, Ze; Jing, Junmeng; Pang, Jie; Hu, Ranyue; Shi, Xingting; Yang, Zhibin; Peng, Suping
Abstract: BaCe0·7 Zr0.1 Gd0.2 O3-δ (BCZG) powder is synthesized by a citrate sol-gel method, and different amounts of Li2 CO3 are introduced to lower the sintering temperature. The densification temperature of BCZG ceramic is decreased drastically to 1250 °C by using Li2 CO3 as sintering aid. BCZG with 2.5 wt% of Li2 CO3 (BCZG-2.5L) can not only remarkably promote the sintering process of BCZG but also enhance its electrical conductivity. The total ionic conductivity of BCZG-2.5L attains to 1.9 × 10 −2  S cm −1 at 600 °C in a wet H2 atmosphere. Ammonia synthesis at atmospheric pressure is conducted on (2K, 10Fe)/Ni-BCZG | BCZG-2.5L | Ni-BCZG electrolytic cell with an applied voltage of 0.2–1.6 V at a temperature of 450–600 °C. The highest NH3 formation rate of 1.87 × 10 −10  mol s −1  cm −2 and the highest current efficiency of 0.53% is achieved at 500 °C with an applied voltage of 0.8 V. Highlights: Effect of Li2 CO3 on sinterability/conductivity of BaCe0·7 Zr0·1 Gd0·2 O3-δ was studied. BaCe0·7 Zr0·1 Gd0·2 O3-δ with 2.5 wt% Li2 CO3 can be well-densified at 1250 °C. High protonic conductivity of 1.9 × 10 −2  S cm −1 was attained on the ceramic material. NH3 formation rate of 1.87 × 10 −10  mol s −1  cm −2 was achieved on the electrolytic cell.